Analysis of Students’ Ability to Develop Critical Thinking Skills Assessment Instruments Using Discussion and Lecture-Based Learning Methods - Rifda Nur Hikmahwati Arif; Ramlawati; Nur Indah Sari; Andi Tri Riski Ramadani (PT. Global Research Collaboration, 2026)
Critical thinking skills are essential competencies in 21st-century education because they support students in analyzing information, evaluating arguments, and making reasoned decisions. In science education, these skills are important not only for understanding scientific concepts but also for solving complex problems and interpreting evidence. However, developing valid and reliable assessment instruments for measuring critical thinking remains a challenge, especially for pre-service teachers. This study aims to analyze the ability of Science Education students to develop critical thinking assessment instruments and to compare the effectiveness of three frameworks: Facione, Watson–Glaser Critical Thinking Appraisal (WGCTA), and Ennis. The research employed a quantitative approach using a descriptive–comparative design involving 27 students enrolled in an assessment instrument development course. Data were collected through the evaluation of instruments developed by students using a validated rubric and analyzed using descriptive and inferential statistical techniques. The results indicate that students demonstrated good ability in developing critical thinking assessment instruments. The average scores were 70.45 for Facione, 82 for WGCTA, and 78.18 for Ennis. The analysis showed no significant difference among the three frameworks, indicating comparable effectiveness in supporting students’ ability to develop critical thinking assessment instruments.